Sumbangan Pendidikan dalam Pembangunan Demokrasi - Sadiyo Sadiyo (Universitas Negeri Malang, 2016)
Education is capable of constructing consciousness and providing knowledge of citizens role in a democratic society. Every citizen, including students, should have a political attitude and ability to take part in a political process. A school is in charge of providing students with the ability to play their role as citizens in a democratic society. Civics education implemented through indoctrination has to be substituted with one given through dialogs based on portofolio to provide democratic expererience for students at school.